2018
DOI: 10.1111/ibi.12572
|View full text |Cite
|
Sign up to set email alerts
|

Apparent resilience of a declining Afro‐Palaearctic migrant to forest loss on the wintering grounds

Abstract: Populations of long‐distance migrant birds are declining but it is unknown what role land cover change in non‐breeding areas may be playing in this process. Using compositional analysis, we assessed habitat selection by one such migrant, the Wood Warbler Phylloscopus sibilatrix, at a wintering site in the forest–savannah transition zone in Eastern Region, Ghana. There was a preference for forest, a habitat that is in marked decline at this site. Annual habitat mapping revealed that the area of forest declined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A recent study showed no change in wood warbler abundance despite habitat conversion, indicating resilience of this species to loss of primary forest at the wintering grounds at least on the short term [28]. The combined knowledge of migration patterns (this study), breeding [26,29] and non-breeding habitat requirements [28,30] as well as other potential impacts at breeding sites [31] will form the basis for effective conservation strategies for declining migratory songbird species such as the wood warbler. Because we could not track spring migration, it remains unknown whether the autumn route is traced back or a more direct route is chosen as indicated by more westerly recoveries in the Mediterranean in spring than autumn [32].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A recent study showed no change in wood warbler abundance despite habitat conversion, indicating resilience of this species to loss of primary forest at the wintering grounds at least on the short term [28]. The combined knowledge of migration patterns (this study), breeding [26,29] and non-breeding habitat requirements [28,30] as well as other potential impacts at breeding sites [31] will form the basis for effective conservation strategies for declining migratory songbird species such as the wood warbler. Because we could not track spring migration, it remains unknown whether the autumn route is traced back or a more direct route is chosen as indicated by more westerly recoveries in the Mediterranean in spring than autumn [32].…”
Section: Discussionmentioning
confidence: 75%
“…Their preferred habitats in both seasons are broadleaved forests with a relatively open forest structure [16,[25][26][27]. A recent study showed no change in wood warbler abundance despite habitat conversion, indicating resilience of this species to loss of primary forest at the wintering grounds at least on the short term [28]. The combined knowledge of migration patterns (this study), breeding [26,29] and non-breeding habitat requirements [28,30] as well as other potential impacts at breeding sites [31] will form the basis for effective conservation strategies for declining migratory songbird species such as the wood warbler.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lower wintering range tree cover, moderate tree felling might not affect the area of suitable habitat negatively (Mallord et al, 2018). This indicates that an otherwise common assumption of niche-tracking might not apply on a fine scale.…”
Section: Contrary To Expectations Individuals Wintering In More Openmentioning
confidence: 99%
“…Tree felling and destruction of natural habitat are widespread throughout Africa. Given the lower wintering range tree cover, moderate tree felling might not affect the area of suitable habitat negatively (Mallord et al, 2018).…”
Section: Contrary To Expectations Individuals Wintering In More Openmentioning
confidence: 99%
“…With the miniaturization of tracking devices we can follow more species throughout their annual cycle, identifying migration routes, staging and wintering areas and even the location of mortality of individuals (Tøttrup et al, 2011; Hewson et al, 2016). Field studies in non-breeding areas have documented habitat preferences and/or tree selection by individual species, such as the wood warbler, or in particular habitats such as the Sahel (Zwarts et al, 2015; Mallord et al, 2018). However, the small sample sizes of fieldwork and tracking studies, particularly in Africa, make it impossible to draw general conclusions about multiple, complex and interacting factors operating over several years and across vast areas.…”
mentioning
confidence: 99%